The role of the lung microbiota and the gut–lung axis in respiratory infectious diseases - Dumas, Alexia; Bernard, Lucie; Poquet, Yannick; Lugo‐Villarino, Geanncarlo; Neyrolles, Olivier (Cellular microbiology, 2018)
The pulmonary microbial community, described only a few years ago, forms a discreet part of the human host microbiota. The airway microbiota has been found to be substantially altered in the context of numerous respiratory disorders; nonetheless, its role in health and disease is as yet only poorly understood. Another important parameter to consider is the gut–lung axis, where distal (gut) immune modulation during respiratory disease is mediated by the gut microbiota. The use of specific microbiota strains, termed “probiotics,” with beneficial effects on the host immunity and/or against pathogens, has proven successful in the treatment of intestinal disorders and is also showing promise in the context of airway diseases. In this review, we highlight the beneficial role of the body's commensal bacteria during airway infectious diseases, including recent evidence highlighting their local (lung) or distal (gut) contribution in this process.